Nutrition Appropriate Generation Great: Education Stunting prevention for Family in Village Cape Oyster Speed North Moramo - Sartini Risky; Mimi Yati; Nikeherpianti Lolok; Eka Dharma Putra; Hellty; Risky Juliansyah; Sri Rahayu; Ardi Naufal Fauzan; Laxmi Adriatik; Putri Mega Wijayanti (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Proper nutrition is a key factor in the formation of a healthy and intelligent generation. However, today there are still many children who are malnourished, causing stunting or growth failure in children. Various efforts have been made by the government and various organizations to address this issue, but the prevalence of stunting remains high. Therefore, it is important to develop and implement effective educational programs to increase family awareness and understanding of the importance of proper nutrition to prevent stunting. Objectives: Activity This aim For develop And evaluate focused educational programs on preventing stunting through enhancement understanding family in the village Cape Oyster about importance proper nutrition. Methods: This research was conducted through counseling to the community with leaflet and powerpoint media. The method used was a cross sectional method, with a one group pre test-post test design approach. The sampling technique is purposive consecutive sampling. Data analysis using univariate analysis using the chi square test. Results: Based of results of the activity, it is known that during the pretest of 15 respondents, 14 respondents (93.3%) had insufficient knowledge, 1 respondent (6.7%) had sufficient knowledge and 0 respondents (0.0%) had good knowledge. While during the posttest, the results showed that respondents with insufficient knowledge were 2 respondents (13.3%), those with sufficient knowledge were 7 respondents (46.7%) and those with good knowledge were 6 respondents (40.0%). Conclusions: The conclusion is that this counseling activity can provide a significant increase in the level of community knowledge related to stunting prevention.